Prevalence of methicillin-resistant Staphylococcus aureus (MRSA) strains among pigs - Odoh, Joshua Atabo; Mela, Luka Ilu; Okolo, Esther; Ogu, Gideon Ikechukwu; Eze, Mary Ebere (Aceh Journal of Animal Science, 2023)
Growing evidence of resistance ofStaphylococcus aureusto methicillin (MRSA) is worrying. Domestic pigs are potential asymptomatic carriers ofS.aureus, including strains resistant to methicillin, which poses a serious threat to meat consumers.This study was therefore aimed at assessing the prevalence ofmethicillin-resistantS. aureus(MRSA) in nasal swaps of selected pigs.This study investigated one hundred and fifty (150) nasal swabs of pigs from fifteen (15) selected pig farms (PGF) within Benin City, Edo State, Nigeria, to assess their levels of exposure toS. aureusandMRSA carriage. Isolation, characterization, and identification of S. aureus and MRSA were done using Mannitol Salt Agar (Oxoid, UK) and Mannitol Salt Agar supplemented with 4g/ml oxacillin, respectively. Antibiotic susceptibility patterns were done using disc diffusion protocols, while presence of MRSA mecA genes was characterised using PCR.Thirty percent (30 %) of 150analyzed swabs were positive forS.aureus, of which 13 (28.9 %) contained MRSA. MRSA were found in nasal swabs of animals from 9different farms. All 13(100%) MRSA isolates contained the mecA gene and were resistant to penicillin, 5 (38.5 %) were resistant to vancomycin and were characterized by multidrug resistance. The results of this study show that 38.5 % of examined pigs were infected with MRSA posing a serious threat to humans.These findings highlight the significant threat posed by MRSA in pigs, raising concerns for human health and emphasizing the importance of effective surveillance and control measures in livestock production to mitigate the transmission of antibiotic-resistant pathogens to consumers. Therefore, it was concluded that the MRSA was detected in pig from 9 different farms, indicating a widespread distribution.